The LuxS Based Quorum Sensing Governs Lactose Induced Biofilm Formation by Bacillus subtilis - Duanis-Assaf, Danielle; Steinberg, Doron; Chai, Yunrong; Shemesh, Moshe (Frontiers in Microbiology, 2016)
Bacillus species present a major concern in the dairy industry as they can form biofilms in pipelines and on surfaces of equipment and machinery used in the entire line of production. These biofilms represent a continuous hygienic problem and can lead to serious economic losses due to food spoilage and equipment impairment. Biofilm formation by Bacillus subtilis is apparently dependent on LuxS quorum sensing (QS) by Autoinducer-2 (AI-2). However, the link between sensing environmental cues and AI-2 induced biofilm formation remains largely unknown. The aim of this study is to investigate the role of lactose, the primary sugar in milk, on biofilm formation by B. subtilis and its possible link to QS processes. Our phenotypic analysis shows that lactose induces formation of biofilm bundles as well as formation of colony type biofilm. Furthermore, using reporter strain assays, we observed an increase in AI-2 production by B. subtilis in response to lactose in a dose dependent manner. Moreover, we found that expression of eps and tapA operons, responsible for extracellular matrix synthesis in B. subtilis, were notably up-regulated in response to lactose. Importantly, we also observed that LuxS is essential for B. subtilis biofilm formation in the presence of lactose. Overall, our results suggest that lactose may induce biofilm formation by B. subtilis through the LuxS pathway.